The Concept of Welfare State in the Light of Islam and Modern World - Akhtar , Dr. Naseem; Akhtar , Dr. Sohail; Sarwer, Dr. Syed Muhammad Nasim (Journal of Quranic and Social Studies, 2021)
The paper primarily deals with welfare state and the topic chosen for this discussion is of great importance in our everyday lives. The state is the territory where we live and enjoy our freedom as a whole. In this assignment It has been tried to discuss the real meaning of a State, the role of state in the life of an individual, the difference between Islamic welfare state and modern welfare State. State is considered as a mother of people due to duties and different aspects of a state, it can be influenced on the common man’s life. The early Islamic state set by the Prophet at Madina was the patronage of the people and modern state also claims as the custodian of People. This paper is a brief discussion, while it explores and highlights the role of state.